HUBUNGAN KECERDASAN GANDA DENGAN HASIL BELAJAR TOPIK ALJABAR SISWA KELAS VIII MTsN 2 PADANGSIDIMPUAN - Rangkuti, Ahmad Nizar (IAIN PADANGSIDIMPUAN, 2015)
Intelligent factor is the most important of human personality, because intelligent take a part in each human activity, specially low or high student’s attainment in learning process. Many influencing factors of someone ability in problem solving. The aim of this researce are to know how the correlation between double intelligent with learning result in math subject about algebra.This research conducted in MTs N 2 Padangsidimpuan at VII. Grade Collecting data done by questionnaire and learning test result. To collect the data about intelligent researcher use questionnaire and test used to collect the student test result. While to test hypothesis. Researcher use correlation product moment, and t-test to see significant or not.Based on research, researcher can conclude there is a significant correlation between, double intelligent with learning result in math subject about algebra in MTs N 2 Padangsidimpuan at VII Grade. Its mean more intelligent kind students have, higher math subject that reach by students.